2007
DOI: 10.1111/j.1365-2621.2006.01242.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of home‐made maize tortilla with soybean

Abstract: Chemical changes of some nutritional components (proximate, mineral and amino acids) and acceptability of traditional process tortillas made from whole maize grain fortified with 30% soybean were evaluated. Inclusion of soybean in tortilla processing improved tortilla quality by modifying protein content and quality. Total ash content was significantly (P < 0.05) increased with processing into tortilla. Soybean has a significantly (P < 0.05) higher phosphorous, potassium, calcium, magnesium and iron than maize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…WAC is the ability of a product to associate with water under limiting condition. It has been suggested that flours with high WAC as seen in this study, will be very useful in bakery products, as this could prevent staling by reducing moisture loss (Obatolu et al, 2007). Water and oil absorption capacities are useful to indicate whether flours can be incorporated into aqueous food formulation especially those involving dough handling.…”
Section: Water Absorption Capacitymentioning
confidence: 89%
“…WAC is the ability of a product to associate with water under limiting condition. It has been suggested that flours with high WAC as seen in this study, will be very useful in bakery products, as this could prevent staling by reducing moisture loss (Obatolu et al, 2007). Water and oil absorption capacities are useful to indicate whether flours can be incorporated into aqueous food formulation especially those involving dough handling.…”
Section: Water Absorption Capacitymentioning
confidence: 89%
“…Commercially formulated complementary foods are often of high cost thus inaccessible to low-income households. Moreover, animal sources of proteins, which are used to complement the cereal based diets are expensive and out of reach for low-income families (Obatolu et al, 2007).…”
Section: Prevalence Of Malnutrition In Ethiopiamentioning
confidence: 99%
“…Soybean (Glycine max (L.) Merr.) is popularly known as a "miracle bean" or a "golden bean" because it is a cheap source of protein (Obatolu et al, 2007). It is an important oil seed, averaging approximately 43% protein and 20% oil by weight (Carrera et al, 2011).…”
Section: Introductionmentioning
confidence: 99%